The Neutron Radiation Analysis On In Vitro/ In Vivo Testing Facility Boron Neutron Capture Therapy - Arrijalu Fadhli Robbi (Indonesian Journal of Physics and Nuclear Applications, 2019)
Boron Neutron Capture Therapy (BNCT) is a radiotherapy method that utilizes the interaction of boron-10 and thermal neutrons that produce lithium particles and alpha particles to kill cancer cells. Before treatment is done to humans, clinical and non-clinical testing is carried out. Non-clinical testing included In Vivo and In Vitro tests. This In Vivo and In Vitro test involves the Kartini reactor as a source and guarantees that the workers and the environment are safe when the reactor is operated. This research is aimed to analyze the neutron radiation after it has passed shielding made from paraffin with aluminum casing in an in vivo/ in vitro testing facility for BNCT. The shielding should withstand neutron radiation so that the radiation dose does not exceed the dose constraint set by PSTA-BATAN at 10 μSv/ hour. In this research, the initial shielding design was in the form of a 2D beam arrangement. For this reason, optimization of each shielding beam form into 3D can be identified. After that, the shieldings were produced and arranged in the radial piercing beamport of Kartini Reactor. The measurement results showed that neutron radiation exposure in the working area around shielding at all measurement points is 0 μSv/ hour , so the results of shielding design calculations can be validated. Neutron radiation exposure was found at 3.78 μSv/ hour and 2.36 μSv/ hour in measurements that were taken between the shielding gaps on the left and right side of the reactor's wall. These measurement results were below the prescribed dose constraint, so the working environment is safe.